Bis[1-(ethoxycarbonylmethyl)pyridinium] bis(1,2-dicyanoethene-1,2-dithiolato-κ(2) S,S′)nickelate(II) - Ren, Tian-li (International Union of Crystallography, 2012)
The asymmetric unit of the title ion-pair complex, (C(9)H(12)NO(2))(2)[Ni(C(4)N(2)S(2))(2)], contains two 1-(ethoxycarbonylmethyl)pyridinium cations and one bis(1,2-dicyanoethene-1,2-dithiolato)nickelate(II) dianion, which exhibits a slightly distorted square-planar coordination geometry. In the crystal, the cations are linked by strong C—H⋯O hydrogen bonds into C(6) chains along [100]. The cations and anions are linked into a three-dimensional architecture by weak C—H⋯N and C—H⋯S interactions.